Urinary schistosomiasis: a forgotten and challenging Diagnosis - Castro,Ana C (2018)
Urinary schistosomiasis is a parasitic disease with a high global burden, especially in poor communities. Although rare in industrialized countries, schistosomiasis is expected to be seen with increasing frequency and poses a diagnostic challenge. We describe three cases of children presenting with gross hematuria caused by Schistosoma haematobium with the purpose of bringing awareness to this uncommon and treatable cause of hematuria in developed countries. All three patients were African male adolescents and presented with terminal hematuria. The long incubation period (as long as 2 years in one of our patients), the differential diagnosis with urinary tract infection prompting prescription of inadequate broad-spectrum antibiotics and the low sensitivity of urine standard examination for the presence of infecting schistosomes were the main challenges in these three patients. To increase the detection rate, urine samples can be taken after a mid-day session of physical exercise and a cystoscopy with tissue biopsies may be required if there are solid masses in the bladder wall on ultrasound. The presented cases aim to show the importance of interdisciplinary collaboration between clinical, surgical specialties and pathologists.